Library Student Employee Expertise: Strategies for Maximizing Your Student Employee Contributions to the Library. Issue 2 (3rd April 2019) - Hogan, Sean; Conlin, Kristin
Abstract : The University of Baltimore Library was recently renovated. Part of the design in the newly renovated space was having one single service point, that we call the Information Desk. This desk serves as the public facing portal for what was previously three public facing service points to services by three separate departments, Academic Success, Access Services and Reference & Instruction. This article describes in depth how our Information Desk Leadership Team encouraged and used our library student employees' expertise and knowledge in the formation of policy and procedure manual, training documents, reference tools and resume lines for use at a single service point.